2021
DOI: 10.1037/sah0000325
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and its related stigma: A qualitative study among survivors in Kampala, Uganda.

Abstract: COVID-19-related stigma is gradually becoming a global problem among COVID-19 survivors with deleterious effects on quality of life. However, this social problem has received little attention in research and policy. This study aimed at exploring the COVID-19-related stigma among survivors in Kampala, Uganda. A cross-sectional exploratory research design was used among COVID-19 survivors in Kampala district. Thirty COVID-19 survivors were examined using in-depth interviews. Data obtained were analyzed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…Most studies in this review observed the psychosocial and economic impacts of the COVID-19 pandemic in LMIC communities around the world [57][58][59][60]63,64,[66][67][68]71,78,80]. The public health literature on pandemics and epidemics of infectious origin is rife with accounts of how these catastrophic disruptions to ordinary life are met by disarray and uncertainty, spawning fear and heightened anxiety [19,20] and often resulting in marginalization and stigma, as communities grapple with unknowns and avoid risks [8,[100][101][102][103][104].…”
Section: Social and Psychological Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies in this review observed the psychosocial and economic impacts of the COVID-19 pandemic in LMIC communities around the world [57][58][59][60]63,64,[66][67][68]71,78,80]. The public health literature on pandemics and epidemics of infectious origin is rife with accounts of how these catastrophic disruptions to ordinary life are met by disarray and uncertainty, spawning fear and heightened anxiety [19,20] and often resulting in marginalization and stigma, as communities grapple with unknowns and avoid risks [8,[100][101][102][103][104].…”
Section: Social and Psychological Effectsmentioning
confidence: 99%
“…The physical quarantining and isolation of suspected or confirmed patients as a means of reducing transmission and mitigating COVID-19 s effects in the community had the unfortunate side effect of generating stigma, discrimination, labeling, and social rejection from the community and families, and on occasion, from healthcare providers [57,60,80]. Actual and symbolic labeling of the houses of quarantined patients, regardless of diagnosis, resulted in protracted avoidance and stigma.…”
Section: Social and Psychological Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The central region is the epicenter of the COVID-19 pandemic with the highest cases of infections, deaths, and recovery. 20 The nurses in the region may be working with critical patients and thus susceptible to PTSD.…”
Section: Methodsmentioning
confidence: 99%
“…Before the COVID-19 pandemic, the Ugandan healthcare system was already under severe strain due to a lack of human resources, poor working conditions, and poor management. 20 At the center of these challenges are nurses, the backbone of the health system and the first point of call for patients. COVID-19 pandemic may have worsened the situation in the country.…”
Section: Introductionmentioning
confidence: 99%